REV7 is required for processing AID initiated DNA lesions in activated B cells - Dingpeng Yang (Nature Portfolio, 2020)
REV7 has emerged as a critical regulator of DNA double-strand breaks repair. Here, the authors show that REV7 is crucial for both antibody class switch recombination and somatic hypermutation in activated B cells, in addition to their survival upon AID-deamination.